ALCAM (CD166) is involved in extravasation of monocytes rather than T cells across the blood–brain barrier. Issue 8 (August 2017) - Lyck, Ruth; Lécuyer, Marc-André; Abadier, Michael; Wyss, Christof B; Matti, Christoph; Rosito, Maria; Enzmann, Gaby; Zeis, Thomas; Michel, Laure; García Martín, Ana B; Sallusto, Federica; Gosselet, Fabien; et al.
Activated leukocyte cell adhesion molecule (ALCAM) has been proposed to mediate leukocyte migration across the blood–brain barrier (BBB) in multiple sclerosis or experimental autoimmune encephalomyelitis (EAE). Here, we confirmed vascular ALCAM expression in human brain tissue samples in situ and on two different human in vitro BBB models. Antibody-mediated inhibition of ALCAM reduced diapedesis of human CD4 + Th1 but not of Th17 cells across the human BBB in vitro. In accordance to human Th1 cells, mouse Th1 cells showed reduced diapedesis across an ALCAM −/− in vitro BBB model under static but no longer under flow conditions. In contrast to the limited role of ALCAM in T cell extravasation across the BBB, we found a contribution of ALCAM to rolling, adhesion, and diapedesis of human CD14 + monocytes across the human BBB under flow and static conditions. Taken together, our study highlights the potential differences in the CNS expression of ALCAM in mouse and human and supports a prominent role for ALCAM in the multi-step extravasation of monocytes across the BBB.